Analysis of HRM Strategy and Job Satisfaction on Increasing Employee Performance - Siti Nadila Tenri Ajeng; Muhammad Asdar; Yunus Amar (Magister Management, Hasanuddin University, 2021)
One of the main factors in the success of a company in achieving its vision and mission is the quality of Human Resources (HR). The purpose of this study was to determine the importance of human resource management strategies and job satisfaction to improve employee performance. In this study, we observe the application of Human Resources to the management of PT KIMA (Persero) by using regression analysis. Data was collected through questionnaire to 20 employees of PT. Industrial Estate of Makassar (PT. KIMA. On the basis of statistical results, the study found that human resource strategy and job satisfaction affect positively and significantly employee performance. The quality and quality of employee performance depend on the policy applied on human resource strategy and satisfaction perceived by employee in relation to their tasks.